Management practices in the institutions of higher education of EU countries for increasing their ratings - F. Rayisa, Yuriy (2020)
The article reveals that there is a trend in the current conditions of globalization and economic development of the world. This tendency determines the development of integration processes between the leading countries of the world. It is pointed out that significant changes are taking place in the higher education systems of European countries. It is proved that each of the educational processes that take place in the educational institution is aimed at achieving a certain kind of result. This result aims to provide quality educational services for all applicants. The main points of view of the scientists concerning studying the experience of management of higher education institutions in Great Britain and France are considered.